Case Report: Severe ophiasis-pattern alopecia areata with concomitant atopic dermatitis in a 5-year-old boy successfully treated with dupilumab - Wei, Zhendong; Yu, Chao; Wang, Aoxue (Frontiers in Pediatrics, 2025)
Alopecia areata (AA) is the third most common reason for dermatological consultations among children. Despite the availability of numerous therapies for AA, including topical and systemic modalities, management options for children diagnosed with severe AA are limited due to the lack of safe and effective treatments suitable for long-term use. Herein, a case involving a 5-year-old boy with severe ophiasis-pattern AA and moderate atopic dermatitis (AD), who was successfully treated with dupilumab, is reported.